(untitled) (Journal of International Studies, 2014)
Economization of foreign policies of super and rising powers as a global trend and an Agenda for Economization of Mongolia’s Foreign relations and its outcomes This article is talks about a macro analysis on economization of foreign policies of super and rising powers as a global trend and an Agenda for Economization of Mongolia’s Foreign relations and its outcomes.